USING THE BLENDED LEARNING AS AN ALTERNATIVE MODEL OF ARABIC LANGUAGE LEARNING IN THE PANDEMIC ERA - Hilmi, Danial; Ifawati, Nur Ila (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2020)
Arabic language learning in the modern era demands mastery of technology in all fields, especially during the Covid-19 pandemic which requires learning assistance. Therefore, the use of blended learning needs to be addressed in the Arabic teaching and learning process. The aim of this study was to describe the implementation of Arabic teaching through blended learning and using blended learning as an alternative model to Arabic language learning in the pandemic era. The study used mixed method that combines qualitative and quantitative approaches descriptively. The data were obtained from interviews, documentation and the results of a survey of the Arabic language learning process obtained from Arabic language teachers. The results showed that the implementation of Arabic language learning through blended learning using a platform that is considered effective according to the conditions of the teacher and students, and the use of blended learning is actually an alternative to implementing face-to-face learning to provide monitoring of language habits.